2009
DOI: 10.1111/j.1365-2702.2009.02912.x
|View full text |Cite
|
Sign up to set email alerts
|

Reexamination of ultra‐thin nipple shield use, infant growth and maternal satisfaction

Abstract: Nipple shield use may facilitate breastfeeding when clinically indicated in maternal-infant dyads without risk of decreased infant weight gain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 15 publications
2
23
0
1
Order By: Relevance
“…The exception to this was nipple shields. The preference for nipple shields is consistent with other studies showing that women are satisfied with their use of nipple shields, indeed, found them indispensible in aiding to achieve breastfeeding goals, and would use them again in the future [31-35]. Nipple shields are unique amongst the repertoire of second-line strategies by facilitating almost direct breastfeeding.…”
Section: Discussionsupporting
confidence: 83%
“…The exception to this was nipple shields. The preference for nipple shields is consistent with other studies showing that women are satisfied with their use of nipple shields, indeed, found them indispensible in aiding to achieve breastfeeding goals, and would use them again in the future [31-35]. Nipple shields are unique amongst the repertoire of second-line strategies by facilitating almost direct breastfeeding.…”
Section: Discussionsupporting
confidence: 83%
“…Another telephone survey conducted by Chertok 16 and published in 2009 evaluated the effect of NSs on infant weight gain. Fifty-four mothers with term infants who had experience nursing with and without an NS were enrolled.…”
Section: Mothers' Experiencesmentioning
confidence: 99%
“…Nipple shields are a technology that consists of a thin, flexible silicone shield that sits atop the mother's areola and nipple to facilitate nipple shape and to enable the infant to maintain a strong latch and suction pattern without slipping off the nipple (Chertok, 2009;Geddes et al, 2008;Hanna, Wilson, & Norwood, 2013;Meier, Furman, & Degenhardt, 2007;Meier et al, 2000). This technology is often associated with preterm infants; however, the application of the nipple shield has spread into the span of interventions to support infants born with congenital anomalies as well as healthy term infants.…”
Section: Nipple Shieldsmentioning
confidence: 97%
“…Any infant who shows signs of immature suction pressure could potentially benefit from the use of a nipple shield. Women report high levels of satisfaction and comfort using a nipple shield as a lactation technology and intervention (Chertok, 2009;Hanna and colleagues 2013). It is important to note that the duration of the intervention is not short term.…”
Section: Nipple Shieldsmentioning
confidence: 97%